2021
DOI: 10.53936/afjare.2021.16(2).10
|View full text |Cite
|
Sign up to set email alerts
|

Gender-differentiated stochastic meta-frontier analysis of production technology heterogeneity among smallholder cassava farmers in Ghana

Abstract: This paper assesses the differences in technical efficiency of, and the cassava production systems employed by, male-managed (MMF) and female-managed (FMF) cassava farms in the Fanteakwa District of Ghana. The study employs the translog stochastic meta-frontier model to analyse data obtained from 300 randomly selected smallholder cassava farmers and finds an average metafrontier technical efficiency (MTE) of 0.06 and 0.03 among MMF and FMF respectively. The technology gap ratios (TGR) are 0.25 and 0.04 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…This implies that a 1% increase in the current level of land employed by farmers results in an increase of about 0.67% in cassava output. These findings are consistent with existing studies of cassava production systems in Africa, which show that land, cuttings, and labor are important determinants of cassava output (Eze and Nwibo, 2014;Dogba et al, 2021;Missiame et al, 2021;Tafesse et al, 2021). Tafesse et al (2021) found that land size, urea fertiliser application and cassava planting material all had a positive and significant effect on cassava production in Southern Ethiopia.…”
Section: Stochastic Production Frontier Modelssupporting
confidence: 89%
See 4 more Smart Citations
“…This implies that a 1% increase in the current level of land employed by farmers results in an increase of about 0.67% in cassava output. These findings are consistent with existing studies of cassava production systems in Africa, which show that land, cuttings, and labor are important determinants of cassava output (Eze and Nwibo, 2014;Dogba et al, 2021;Missiame et al, 2021;Tafesse et al, 2021). Tafesse et al (2021) found that land size, urea fertiliser application and cassava planting material all had a positive and significant effect on cassava production in Southern Ethiopia.…”
Section: Stochastic Production Frontier Modelssupporting
confidence: 89%
“…This finding aligns with that of Missiame et al (2021), who found that access to extension services improves the technical efficiency of smallholder cassava farmers in Ghana. Lastly, the coefficients of distance to market and district headquarters were positive and significant across the three countries.…”
Section: Determinants Of Technical Inefficiencysupporting
confidence: 89%
See 3 more Smart Citations